Irisin mRNA and circulating levels in relation to other myokines in healthy and morbidly obese humans - Vamvini, Maria T.; Aronis, Konstantinos N.; Panagiotou, Grigorios; Huh, Jooyoung; Chamberland, John P.; Brinkoetter, Mary T.; Petrou, Michael A.; Christophi, Costas A.; Kales, Stefanos N.; Christiani, David C.; Mantzoros, Christos S. (My University, 2013)
Objective: Skeletal muscle is considered to be an endocrine organ that secretes a number of myokines including follistatin (FST), myostatin (MSTN), activin A, and the newly identified irisin. Irisin's biology and function exhibit similarities with the functions of the FST-MSTN-activin A axis. It remains unknown whether there is any interplay among these molecules. The aim of this study is to examine potential associations of irisin with the FST, MSTN, and activin A axis. Methods: Two observational studies were performed to evaluate the associations of irisin with the other three peptides. Study A included 150 healthy males aged 18.48G0.16 years with BMI 23.18±3.75 kg/m2. Fasting serum samples were used to measure the levels of the molecules of interest. Study B included 14 morbidly obese individuals, candidates for bariatric surgery, aged 53.14±8.93 years with BMI 50.18±10.63 kg/m2. Blood samples were obtained after an overnight fast. Eight out of the 14 participants consented to an optional thigh biopsy during their bariatric surgery. Using the above blood and tissue samples, we measured circulating levels and muscle mRNA of irisin, FST, MSTN, and activin A. Results: We report that FNDC5 mRNA in muscle is positively correlated with FST mRNA expression in morbidly obese subjects (ρ=0.93, P<0.001). We also found that circulating irisin is positively correlated with FST circulating levels among lean subjects (ρ=0.17, P=0.05) while this association was suggestive among the obese (ρ=0.56, P=0.07). Conclusion: The newly identified myokine irisin may be positively associated with FST at both the mRNA and circulating protein level.
Keywords: Skeletal muscle; MRNA; Myostatin (MSTN)